2022
DOI: 10.3390/jcm11185293
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bariatric-Surgery-Induced Weight Loss on Patients Undergoing Liver Transplant: A Focus on Metabolism, Pathophysiological Changes, and Outcome in Obese Patients Suffering NAFLD-Related Cirrhosis

Abstract: Because of their condition, patients with morbid obesity develop several histopathological changes in the liver, such as non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), cirrhosis, and end-stage liver disease (ESLD). Hence, a liver transplant (LT) becomes an opportune solution for them. Due to many challenges during the perioperative and postoperative periods, these patients are recommended to lose weight before the surgery. There are many proposals to achieve this goal, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Immunosuppressive therapy after allograft solid organ transplantation is required to prevent rejection and preserve organ function (40)(41)(42)(43). Various combinations of currently approved agents are needed to obtain the patients' tailored regimens to balance adequate immunosuppression with drugs' side effects (44)(45)(46)(47) through continuous titration to reduce their side effects due to their narrow therapeutic index (48)(49)(50)(51). In this light, a reliable drug supply chain is even more urgent due to the risk of counterfeit medications.…”
Section: Drugsmentioning
confidence: 99%
“…Immunosuppressive therapy after allograft solid organ transplantation is required to prevent rejection and preserve organ function (40)(41)(42)(43). Various combinations of currently approved agents are needed to obtain the patients' tailored regimens to balance adequate immunosuppression with drugs' side effects (44)(45)(46)(47) through continuous titration to reduce their side effects due to their narrow therapeutic index (48)(49)(50)(51). In this light, a reliable drug supply chain is even more urgent due to the risk of counterfeit medications.…”
Section: Drugsmentioning
confidence: 99%
“…Nonetheless, weight reduction occasionally comes at the expense of malnourishment and the difficulties that accompany it 10 . Furthermore, its impact on liver function, particularly potential effects on non-alcoholic fatty liver disease (NAFLD), has not yet been extensively examined 11 . Up to 90% of these individuals have NAFLD, which is very common and varies from moderate fatty liver alterations and steatosis to non-alcoholic steatohepatitis (NASH), with the potential to proceed to liver fibrosis with persistent disease 12 .…”
Section: Introductionmentioning
confidence: 99%
“…With the aim to obtain moderate weight loss and liver volume and steatosis reduction before BS, several dietary protocols have been introduced over time, among them very low-calorie diets (VLCDs) and very low-calorie ketogenic diets (VLCKDs) are widely prescribed [ 8 , 9 , 10 , 11 , 12 ]. In particular Schiavo et al, have shown that a 4-week preoperative ketogenic diet is safe and effective at reducing body weight (−10.3%, p < 0.001, in males; −8.2%, p < 0.001, in females) and the left hepatic lobe volume (−19.8%, p < 0.001) in patients with obesity scheduled for BS [ 13 ]. Furthermore, Albanese et al, aiming to compare surgical outcome and weight loss in two groups of patients who were offered two different pre-operative kinds of diet (VLCD and VLCKD), reported that VLCKDs showed better results than VLCDs on surgical outcome, influencing the drainage output, post-operative hemoglobin levels, and hospital stay [ 14 ].…”
Section: Introductionmentioning
confidence: 99%